There Is No Crime for Those Who Have Christ Religious Violence in the Christian Roman Empire - Gaddis, Michael 1970- (Berkeley University of California Press, 2005)
Preface and Acknowledgments; List of Abbreviations; Introduction; 1. "What has the emperor to do with the church?" Persecution and Martyrdom from Diocletian to Constantine; 2. "The god of the martyrs refuses you": Religious Violence, Political Discourse, and Christian Identity in the Century after Constantine; 3. An Eye For An Eye: Religious Violence in Donatist Africa; 4. Temperata Severitas: Augustine, the State, and Disciplinary Violence; 5. "There is no crime for those who have Christ": Holy Men and Holy Violence in the Late Fourth and Early Fifth Centuries
There is no crime for those who have Christ," claimed a fifth-century zealot, neatly expressing the belief of religious extremists that righteous zeal for God trumps worldly law. This book provides an in-depth and penetrating look at religious violence and the attitudes that drove it in the Christian Roman Empire of the fourth and fifth centuries, a unique period shaped by the marriage of Christian ideology and Roman imperial power
Keywords: Martyrdom; Church History -- 5th century; Church History -- 4th century; Violence -- Religious aspects -- Christianity; Persecution; RELIGION ; Christian Church ; History; RELIGION ; Christianity ; History; HISTORY ; Ancient ; General; Church History; Violence ; Religious aspects ; Christianity